Formasi Strategi di Organisasi Profesional - Jane, Orpha (Jurnal Administrasi Bisnis, 2011)
Strategy formation within every organization has a unique characteristics. Profes-sional organizations are an organization that contains number of individuals with aspecific competency and capability. Also its have a structure with a team of expertrather than technostructure. This type of organization, all the member of the organi-zations are involved in formulating the strategy. Top leader has a role as coordinatorin formulating and executing the strategy.Keywords: strategy, strategy process and formation, professional organization